(untitled) (Bangladesh Journal of Botany, 2023)
Effects of vermicompost and chemical fertilizers on the concentration and uptake of NPKS in different organs as well as well as oil content of sunflower (cv. BARI-2) were evaluated. The experiment consisted of 16 treatments, viz.: VC1 Control, VC2, VC3, VC4, VC5, VC6, VC7, VC8, VC9, VC10, VC11, VC12, VC13, VC14, VC15 and VC16. Results showed that the concentration, uptake of macronutrients (NPKS) and oil content of seeds of the crop increased significantly (P< 0.05) with increasing rate of the amendments over the control in most of the cases. Combination of the treatments showed better performance than their individual application. Maximum values of NPKS concentration in different organs of sunflower were 0.42, 0.23, 1.95 and 0.12% for stem., 0.57, 0.33, 2.66 and 0.20% for root., 2.61, 0.42, 2.77 and 0.19% for leaf., 2.30, 0.65, 2.65 and 0.20% for petiole., 0.76, 0.71, 2.21and 0.26% for inflorescence and 4.86, 0.69, 1.08 and 0.16% for seed were recorded in treatments 5t VC ha-1 +N120P90K150 kg ha-1 and 7.5t VC ha-1 +N120P90K150 kg ha-1, respectively in most of the cases. Significantly (P < 0.05%) the highest content of oil (46.9%) in seed was found in the treatment 7.5t VC ha-1 +N80P60K100 kg ha-1. The overall findings of this study indicated that vermicompost in combination with chemical fertilizers could be applied to achieve better yield of sunflower in the costal belt of Bangladesh. Bangladesh J. Bot. 52(1): 149-157, 2023 (March)